Energy efficient routing for wireless sensor networks with grid topology - Goh, Hock Guan; Sim, Moh Lim; Ewe, Hong Tat (Springer Berlin Heidelberg, 2006)
Agricultural monitoring using wireless sensor networks has gained much popularity recently. In this paper, we review five existing flat-tree routing algorithms and proposed a new algorithm suitable for applications such as paddy field monitoring using wireless sensor network. One of the popular data collection methods is the data aggregation approach, where sensor readings of several nodes are gathered and combined into a single packet at intermediate relay nodes. This approach decreases the number of packets flowing and minimizes the overall energy consumption of the sensor network. However, most studies in the past do not consider the network delay in this context, which is an essential performance measure in real-time interactive agricultural monitoring through Internet and cellular network. We propose an algorithm called Information Selection Branch Grow Algorithm (ISBG), which aims to optimize the network in achieving higher network lifetime and shortening the end-to-end network delay. The performance of this algorithm is assessed by computer simulation and is compared with the existing algorithms used for data aggregation routing in wireless sensor networks.